(A)Symmetric effects of changes in the saving rate on the investment rate in Norway: 1830–2017. Issue 11 (25th June 2021) - Bineau, Yannick
ABSTRACT: In view of the Feldstein–Horioka (1980) puzzle, this study examines the relationship between the investment rate and the saving rate using annual data from Norway for 1830 to 2017. The nonlinear version of the autoregressive distributed lag (ARDL) cointegration methodology developed by Shin (2014), based on the linear ARDL bounds cointegration testing approach of Pesaran et al. (2001), is implemented. The findings show that there is a long-term cointegration relationship between the saving rate and investment rate. The nonlinear ARDL model indicates that there are short-run but no long-run asymmetric effects. It is concluded that Norway respects its intertemporal budget constraint and that international capital mobility is high.